A karyotype comparison between two species of bordered plant bugs (hemiptera, heteroptera, largidae) by conventional chromosome staining, c-banding and rDNA-FISH - Salanitro, Lucila Belén (2017)
A cytogenetic characterization, including heterochromatin content, and the analysis of the location of rDNA genes, was performed in Largus fasciatus Blanchard, 1843 and L. Rufipennis Laporte, 1832. Mitotic and meiotic analyses revealed the same diploid chromosome number 2n = 12 + X0/XX (male/female). Heterochromatin content, very scarce in both species, revealed C-blocks at both ends of autosomes and X chromosome. The most remarkable cytological feature observed between both species was the different chromosome position of the NORs. This analysis allowed us to use the NORs as a cytological marker because two clusters of rDNA genes are located at one end of one pair of autosomes in L. Fasciatus, whereas a single rDNA cluster is located at one terminal region of the X chromosome in L. Rufipennis. Taking into account our results and previous data obtained in other heteropteran species, the conventional staining, chromosome bandings, and rDNA-FISH provide important chromosome markers for cytotaxonomy, karyotype evolution, and chromosome structure and organization studies.